(untitled) (Prostor, 2024)
Most of Europe’s housing was built between 1945 and 1975. This detailed compendium of post-war housing presents 54 selected estates and buildings from across Europe in order to examine how this renewal process was implemented. A comparison between projects reveals universal themes, as well as local aspects integrated into the architecture. This study forms the basis for a new assessment of buildings from this period. The projects featured are highly diverse, experimental and locally specific.